Integrated Approach of Geotechnical and Geophysical Investigations into Failed Segments of the Road Along Vwei (Mararaban Jama’a) - Mangu Road. North-Central Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2025)
The aim of this study is to examine the subsurface structural disposition and provideuseful information on the soil properties with a view to proffer solution and avertfuture road failure occurrences. A combined scientific approach of remote sensing,geophysical and geotechnical investigations on the earth materials within andaround those failed segments have become a fundamental tool to discovering thefactors responsible for the insistent problems. Vertical Electrical Soundings (VES)probe of the failed portions gave three (3) to four (4) layered earth interpreted tocontain clayey-sand and loose saturated sand units at the upper portion, highlysaturated weathered/fractured basement and fresh basement at the lower portion.The resistivity values for the top soil is 139Ωm - 366Ωm, weathered layer is 20Ωm-101Ωm, weathered/fractured layer is 30Ωm - 473Ωm and fresh basement is 284Ωm- ∞Ωm. The thickness of the top soil is 0.6m - 1.9m, weathered layer is 5.4m to39.1m, weathered/fractured layer is 2.0m - 25.8m and fresh basement 11.1m -39.4m respectively. CBR result range from 23.40 – 36.40%, indicating percentagereduction in strength with wetness of 43.7% - 50.8%. Liquid limit, linear shrinkageand plastic limit index gave values in the range of 28.0 - 47.5%, 3.6 - 10.7%, 11.4 -18.9% respectively. This study implies that integrated structural geology,geophysical and geotechnical investigations offer very useful approach forcharacterizing near surface earth and thus can help in preparation beforeengineering structures are found on same.